Challenges, changes, alternatives for SMES (and the theory of "degrowth") - István Takács; Katalin Takács-György (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
To find and adopt those products, solutions, technologies that are suitable for profitable production and ensure viability at the same time is one of the basic tasks of sustainable economy. Viable enterprise means to earn enough revenue to cover all the costs, including the costs of investment and innovation, to operate in an effective way, to "balance" (equilibrate) with the limited resources, (natural, renewable) notwithstanding the limitation of growth. In the study the new paradigm of "degrowth" is examined along the potential alternatives opened for SMEs, based on thoughts of Serge Latouche. In the paper it is summarized the main characteristics of innovative strategies for SMES in agriculture, too. The new values (Réévaluer - reappraise) suggest the intent of preserving the nature at least in the nowadays condition. Precision agriculture is a tool in this and allows the efficient use of natural resources (Restructurer - restructuring factors of production). Each farming strategy in which the farmers' cooperation is the base of an efficient machinery use (Restructurer - restructuring of social relationships), each technology that reduces the human-health risk (Réduire - reduction) shows into the direction of degrowth. We believe that we will not be able to carry out sustainable economy without strengthening the SMEs, helping them to find their successful way/strategy on development, being innovative and to cooperate with each other. Values, attitudes, networks, trust, openness are important to both individual and social utility coincidence that promotes the sustainability of being viable, competitive in wider meaning: future orientation, ability to renew (development, imitation, synthesis), economic/social cooperation.
Keywords: M29; Q01; Y50; 330; sustainable economy; innovation; SMEs